An explanation of the microcrack formation in Li1.3Al0.3Ti1.7(PO4)3 ceramics. Issue 8 (July 2016) - Waetzig, Katja; Rost, Axel; Langklotz, Ulrike; Matthey, Björn; Schilm, Jochen
Abstract: A ceramic material of lithium aluminum titanium phosphate (LATP) with the composition of Li1.3 Al0.3 Ti1.7 (PO4 )3 was prepared by melting Li2 CO3, Al2 O3, TiO2 and 85% H3 PO4, milling the glass ceramic plate in two steps and sintering the powder between 800 and 1050 °C by Spark Plasma Sintering (SPS). The phase composition, density and porosity as well as the ionic conductivity of the specimens were measured. The highest density (2.82 g/cm 3 ) without open porosity and an ionic conductivity (∼1 × 10 −4  S/cm) was reached between 900 and 1000 °C. At first, initial microcracks were observed at the interfaces of the AlPO4 secondary phase at 950 °C. Sintering temperatures above 1000 °C lead to coarse grains and numerous cracks at the grain boundaries of the different phases dominate the microstructure. In this study, two different mechanism of cracking are found and an explanation of their formation is given.